Partitioning Medical Image Databases for Content-based Queries on a Grid - Montagnat, J.; Breton, V.; Magnin, I. E. (Methods of Information in Medicine, 2005)
Objectives: In this paper we study the impact of executing a medical image database query application on the grid. For lowering the total computation time, the image database is partitioned into subsets to be processed on different grid nodes.Methods: A theoretical model of the application complexity and estimates of the grid execution overhead are used to efficiently partition the database.Results: We show results demonstrating that smart partitioning of the database can lead to significant improvements in terms of total computation time.Conclusions: Grids are promising for content-based image retrieval in medical databases.
Keywords: Medical images; content-based retrieval; databases search; Grid computing